The therapeutic effects of naringenin on bronchial pneumonia in children - Wenjing Yao; Xiaopeng Zhang; Feng Xu; Chunxia Cao; Tongtong Liu; Yuanyuan Xue (Wiley, 2021)
Abstract Bronchial pneumonia in children is a common infectious disease in toddlers and infants, which may cause hyperpyrexia, pulmonary moist rales, and even respiratory failure. Traditional drugs for bronchial pneumonia in children often lead to drug resistance and side effects. Recently, naringenin has been reported to be a potential treatment for several airway inflammatory diseases due to its anti‐inflammatory and anti‐microbial activities. The current clinical study aimed to evaluate the safety and therapeutic effect of naringenin in treating bronchial pneumonia in children. A total of 180 eligible patients were randomly assigned into naringenin (NAR) group and azithromycin (AZI) group. All participants were required to follow a 5‐day oral administration, and their serum cytokine levels were measured during the clinical intervention. After the treatment, the disappearance time of clinical symptoms, and the incidences of complications and adverse reactions were compared between the two groups. Naringenin was able to inhibit inflammation, shorten the disappearance time of clinical symptoms, reduce the incidences of bronchial pneumonia complications and related adverse reactions, and improve the health conditions of the patients. Our results suggested that naringenin was safe and beneficial to children with bronchial pneumonia, providing new insights into the clinical application of naringenin.